Stories that bridge us: A mixed methods study to understand the impact of a hospital-wide storytelling event. - Maria F Nardell; Malini M Gandhi; Barbara Sarnoff Lee; Amy Wasserman (PLoS ONE)
Oral storytelling events for healthcare professionals are gaining in popularity, yet evaluation of these initiatives is scarce. We designed and assessed the impact of a hospital-wide storytelling event at an academic medical center in New England. This study was grounded in social constructivism, which posits that knowledge and collaborative meaning-making are socially constructed through interpersonal interactions and shared language. Stories were solicited from interdisciplinary staff on a theme, and six selected storytellers were paired with coaches. The hybrid in-person/virtual event was held in 2021. Attendees were invited to complete a post-event survey, as well as a semi-structured interview or written response. Storytellers were invited to reflect via a post-event focus group or written responses. Qualitative data were coded using a mixed inductive and deductive content analytic approach. Survey data were analyzed using descriptive statistics. The storytellers included representation from internal and emergency medicine, nursing, infrastructure project management, and research administration. The 155 attendees included 25 in-person/130 virtual. Qualitative data (nine participants) revealed that sharing stories fostered interpersonal connection and a sense of common humanity, enhanced by the storytellers' vulnerability and diversity. Storytellers valued coaches' emotional and creative support in co-creating stories with them. Lastly, the event was felt to strengthen the hospital community. These themes were echoed in the survey data (30 participants): > 75% of respondents indicated that the event helped them reflect on their values, connect with others, and access a sense of purpose. A multidisciplinary hospital-wide oral storytelling event is one way to enhance self-reflection, interpersonal connection, and a sense of community among healthcare professionals.